The influence of modification on the structure and mechanical properties of aluminum alloys - Tetiana Nosova; Stella Mamchur (Challenges and Issues of Modern Science)
The purpose of this work is to form the structure of an aluminum alloy for the brake housing of a wind power plant under given operating conditions. Mechanical impacts associated with the operation and transportation of products include overloads, vibrations, shocks, and acoustic loads. Climatic influences are characterized by the following components: temperature, pressure, humidity, dust. In addition to climatic and mechanical influences, chemical, biological, radiation, magnetic, electrical, and electromagnetic influences are possible. Ensuring resistance to mechanical, climatic and other influences is necessary for the normal functioning of mechanisms, components and parts. Requirements for objects are determined by the conditions of their operation. Two main groups of influences can be distinguished: mechanical and climatic.Mechanical impacts associated with the operation and transportation of products include overloads, vibrations, shocks, and acoustic loads. Climatic impacts are characterized the following components: temperature, pressure, humidity, dust. In addition to climatic and mechanical influences, chemical, biological, radiation, magnetic, electrical, and electromagnetic influences are possible. Ensuring resistance to mechanical, climatic and other influences is necessary for the normal functioning of mechanisms, components and parts.When comparing aluminum alloys, for example AL4S, AL5, AL9, the AL4S alloy has the best manufacturability (high ductility). The necessary plasticity is needed so that when drilling holes for the bolts (alternating and fatigue loads occur), thanks to which the housing is attached to the gearbox, the part does not collapse. In AL9, the ductility is the same as in AL4S, but the yield strength is significantly lower. Exposure to seawater and fog leads to the formation on the surface of a part of a conductive medium and in the case of a potential difference caused by structural heterogeneity, corrosion destruction may occur (due to the appearance of a liquid conductive film of a salt solution). As a result, the tensile strength increased from 240 MPa to 270 MPa, hardness - from 70 HB to 85 HB, ductility - from 4% to 6%.